Pre-disaster Efforts for Flash Floods in De Flamboyan Housing, Tanjung Selamat Village, Medan Tuntungan District in 2023 - Amilia Isyana; Myrnawati Crie Handini; Elsarika Damanik (SEAN Institute, 2023)
The purpose of this study is to know and analyze the efforts in the “De Flamboyan” housing area of ​​Tanjung Selamat Village in the pre-disaster flash flood management. The type of research is qualitative research. Research data collection was conducted by FGD, in-depth interviews and direct observation. The informants in this study were the village head, the head of the government section, the village fund manager and two residents who were at risk of flash floods. In this study, triangulation was carried out by asking the same question to informants three times at different times and by looking at written documents and conditions in the field to find out the validity of the interview results. Processing research data with the Miles Hubberman method. The results of the study were flash flood mitigation efforts carried out in the “De Flamboyan” housing area in Tanjung Selamat Village. Flash flood management efforts in the “De Flamboyan” housing area Tanjung Selamat Village is the government with BPBD Medan City puts water level sensor in the ditch, disaster area marker in front of the housing area; the government with BWS II rebuilt damaged boundary walls called “gabions”, the resident moved in another place, providing gathering point houses, placing valuables in higher locations, preparing buoys, carrying out the cooperation to clean the river, the ditches and the housing area . disaster area marker in front of the housing area; the government with BWS II rebuilt damaged boundary walls called “gabions”, the resident moved in another place, providing gathering point houses, placing valuables in higher locations, preparing buoys, carrying out the cooperation to clean the river, the ditches and the housing area . disaster area marker in front of the housing area; the government with BWS II rebuilt damaged boundary walls called “gabions”, the residents moved in another place, providing gathering point houses, placing valuables in higher locations, preparing buoys, carrying out the cooperation to clean the river, the ditches and the housing area .